2011
DOI: 10.1111/j.1438-8677.2011.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological aspects of plant selenium hyperaccumulation

Abstract: Hyperaccumulators are plants that accumulate toxic elements to extraordinary levels. Selenium (Se) hyperaccumulators can contain 0.1-1.5% of their dry weight as Se, levels toxic to most other organisms. In this review we summarise what is known about the ecological functions and implications of Se (hyper)accumulation by plants. Selenium promotes hyperaccumulator growth and also offers a plant several ecological advantages through negative effects on Se-sensitive partners. High tissue Se levels reduce herbivory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 58 publications
4
72
0
1
Order By: Relevance
“…Generally, most cultivated plants contain less than 25 mg Se kg −1 DWs and are considered to be non-accumulators [31]. More recently, it was revealed that most plant species growing on seleniferous soils contain <10 mg Se kg −1 DWs, and experience toxicity at levels above ~100 mg Se kg −1 DWs [32]. Therefore, from our results it can be suggested that the flue-cured tobacco had a low tolerance to high Se levels, an should be classified as a Se non-accumulator.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, most cultivated plants contain less than 25 mg Se kg −1 DWs and are considered to be non-accumulators [31]. More recently, it was revealed that most plant species growing on seleniferous soils contain <10 mg Se kg −1 DWs, and experience toxicity at levels above ~100 mg Se kg −1 DWs [32]. Therefore, from our results it can be suggested that the flue-cured tobacco had a low tolerance to high Se levels, an should be classified as a Se non-accumulator.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive intake of Se causes garlic breath odor, hair and nail loss, skin and nervous system disorders, and other symptoms (Zhu et al 2009). Additionally, the concentrations of Se in most plants are above 100 mg kg −1 , which also cause damage (El Mehdawi and Pilon-Smits 2012). Therefore, controlling the uptake of Se by plants from the environment (soils) is crucial to reduce the health risk of both Se toxicity and deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that Se hyperaccumulation evolved as a defense mechanism against herbivory. Se can protect plants from a wide variety of Se-sensitive invertebrate and vertebrate herbivores, due to deterrence and toxicity (for review, see Boyd, 2007Boyd, , 2010Quinn et al, 2007;El Mehdawi and Pilon-Smits, 2012). Se has been shown to protect plants from aphids (Hurd-Karrer and Poos, 1936;Hanson et al, 2004), moth and butterfly larvae (Vickerman et al, 2002;Hanson et al, 2003;Freeman et al, 2006a), crickets and grasshoppers , thrips and spider mites , and prairie dogs Freeman et al, 2009).…”
mentioning
confidence: 99%